Circulação de Imagens Lusitanas no Além-Mar: Cultura Histórica e Cultura Artística na azulejaria barroca de Teotónio dos Santos na Paraíba Colonial - Nóbrega, Michael Douglas dos Santos (2015)
This MsC thesis analyzes the circulation of Lusitanian images in Overseas through tiles panels which shows the Joseph of Egypt’s saga, whose authorship is attributed by experts to the Portuguese tile master Teotónio dos Santos – active in Lisbon during the 1730’s – and is installed in the Franciscan convent built in the Paraíba captaincy during the colonial period, between the 17thand 18thcenturies. Walking through the fields of Cultural History, the Historical Culture and specialized historiography of tiles art, focusing on Paraíba, this work intends to establish a comparison of others panels of this craftsman with the same theme, some of them preserved in Lusitanian Atlantic islands and in Portugal itself, tracing its author style trajectory, trying to identify the iconographic sources of his work and also discusses the movement of iconographic models in Portuguese America.